ANALYSIS OF SHALLOW SUBSURFACE STRUCTURE AT GEOTHERMAL AREA OF IE JUE USING RESISTIVITY METHOD - Syafrizal Idris; Muhammad Syukri; Muhammad Syukri Surbakti; Marwan .; Muchlis .; Ibnu Rusydy; Nurul Aflah (Jurnal Natural, 2018)
It has been conducted a geo-electrical resistivity survey at geothermal area of Ie Jue, Aceh Besar.  The survey aims to measure resistivity value in the area. It is expected that the values of resistivity will image the subsurface structure in the area. In addition geological features in the area are shown after we process it. The data acquisition in this study was acquired using a SuperSting R8/IP resistivitymeter and its data processing using EarthImager 2D software to get the image of resistivity pseudosection. The two lines of measurement crossed the surface geothermal manifestation. Each line has 330 m in length, and 56 electrodes with electrode space of 6 m. The result of resistivity pseudosection model interpreted based on geological condition and observation in the area. Resistivity pseudosection model shows the study is water-saturated (64.0 Ωm) to a depth of ±65 m and a highly conductive zone (0.6-3.5 Ωm) with a thickness of 30-50 m. This conductive layers below the embodied surface at a distance of 158-160 m on the IJ-Y1 line and at a range of 130-185 m on the IJ-Y2 line. This conductive zone is indicated as a weak zone where geothermal fluids are transported to the surface.Keywords: Geothermal, Ie Jue, geo-electrical resistivity survey, resistivityREFERENCES          Bennet, J.D., Bridge, D.McC., Cameron, N.., Djunuddin, A., Ghazali, S.A., Jeffrey, D.H., Kartawa, W., Rock, M.N.S., Thomson, S.J., Whandoyo, R., 1981. PetaGeologiLembar Banda Aceh, Sumatera, Puslitbang Geologi. Bandung.Syukri, M., Saad, R., Nordiana, M., Azwin, I. 2014. Preliminary Study of Sumatera Fault Using 2-D Resistivity Imaging Method. Electronic Journal of Geotechnical Engineering, 19.Knödel, K., Lange, G., Voigt, H.J., 2007. Environmental geology: Handbook of field methods and case studies: Springer Science Business Media.Telford, W. M., Geldart, L. P., Sheriff, R. E. 1990. Applied Geophysics Second Edition, Cambridge University Press, USAMarwan, M., Rusydy, I., Nugraha, G.S. and Asrillah, A., 2014. Study of Seulawah Agam’s Geothermal Source Using Gravity Method. Jurnal Natural, 14(2)Asrillah, A., Marwan, M., Rusydy, I. and Nugraha, G.S., 2014. Application of Magnetics Method to Mapping the Geothermal Source at Seulawah Agam Area. Jurnal Natural, 14(2).Ismail, N.,Ramadhan, S., 2013. Karakterisasi Struktur Dangkal pada Lapangan Panas Bumi Seulawah Agam Menggunakan Metode Very Low Frequency (VLF). Prosiding Semirata FMIPA Universitas Lampung. Lampung, Indonesia.